Phenotyping of corn plants with effect of mesotrione herbicide - Ramírez-Rojas, Christian; Peña-Valdivia, Cecilia Beatriz; García-Esteva, Antonio; Padilla-Chacón, Daniel (Revista Mexicana de Ciencias Agrícolas, 2022)
Mesotrione is an herbicide that is used for the control of a wide spectrum of weeds during pre- and post-emergence in the crop of corn (Z. mays L). The objective of the present study was to evaluate the effects of mesotrione on growth, pigmentation, with images in the visible spectrum (red, green, and blue, RGB) and fluorescence (Fv/Fm) in the corn cultivars Cacahuacintle, HS-2 and Vitamaíz. The plants were grown in greenhouses, in the College of Postgraduates, Montecillo Campus during 2020, they were analyzed in the vegetative stage V3-V4 with a design of randomized complete blocks and with factorial arrangement. The treatments evaluated were controls (water and adjuvant without mesotrione) and mesotrione 1X and 2X. Ten days after application, images of the plants were obtained, which were analyzed with the LemnaGrid program. None of the mesotrione doses altered the growth of the cultivars, although there were effects on the color of the plants. The loss of green color (chlorosis) occurred in more than 50% of the base of the leaf blade and with spots at the apex. The images of chlorophyll fluorescence and the Fv/Fm index in leaf fragments indicated that the highest dose of mesotrione (2X) in the cultivars Cacahuacintle and Vitamaíz maintained values similar to the controls; in contrast, in HS-2 those values decreased. The results of the present study demonstrated the usefulness of non-invasive phenotyping with RGB images, and of the chlorophyll fluorescence to evaluate the effect of herbicides on crops.